Physical chemistry : multidisciplinary applications in society - Schmitz, Kenneth S., 1943- (Elsevier, 2018)
The advancements in society are intertwined with the advancements in science. To understand how changes in society occurred, and will continue to change, one has to have a basic understanding of the laws of physics and chemistry. Physical Chemistry: Multidisciplinary Applications in Society examines how the laws of physics and chemistry (physical chemistry) explain the dynamic nature of the Universe and events on Earth, and how these events affect the evolution of society (multidisciplinary applications). The ordering of the chapters reflects the natural flow of events in an evolving Universe: Philosophy of Science, the basis of the view that natural events have natural causesiŽ- Cosmology, the origin of everything from the Big Bang to the current state of the UniverseiŽ- Geoscience, the physics and chemistry behind the evolution of the planet Earth from its birth to the presentiŽ- Life Science, the molecules and mechanisms of life on EarthiŽ- Ecology, the interdependence of all components within the Ecosphere and the UniverseiŽ- Information Content, emphasis on how words and phrases and framing of issues affect opinions, reliability of sources, and the limitations of knowledge.